Effect of Moringa Oleifera Leaf Extract on FGF21 mRNA Expression in Male Wistar Rats’ Skeletal Muscle Under Sedentary Condition - Nurhayati, Titing; Lolinhandary, Karen (Althea Medical Journal, 2025)
Background : Fibroblast growth factor 21 (FGF21) is a muscle-derived myokine whose expression changes in response to elevated reactive oxygen species (ROS), primarily generated by cytochrome c oxidase complex IV (COX IV) in skeletal muscle. Moringa oleifera (MO) is known for its antioxidant potential, which may influence FGF21 expression and oxidative stress pathways. This study aimed to evaluate the effects of MO leaf extract on FGF21 mRNA expression and mitochondrial oxidative capacity in skeletal muscle under sedentary conditions. Methods:  This semiquantitative analytic study used 10 sedentary male Wistar rats, divided into control and treatment groups. The treatment group was administered 200 mg/kg of MO leaf extract, while the control group was given a standard diet and water for 12 weeks. COX IV and FGF21 mRNA levels in the soleus muscle were measured using real-time polymerase chain reaction. Statistical analysis included the Shapiro–Wilk normality test, Levene’s homogeneity test, independent t-test, or Mann–Whitney test, with significance set at p<0.05.Results: The treatment group exhibited lower COX IV (0.6414 vs 0.7388) and higher FGF21 (0.9414 vs 0.7157) mRNA levels compared to the control group; however, the differences were not significant (p=0.354 and p=0.170, respectively). Conclusions: Although FGF21 may act as a therapeutic response to decreased mitochondrial activity, MO supplementation in sedentary conditions shows no significant effect on mitochondrial oxidative function or FGF21 expression. Nonetheless, these findings contribute to understanding metabolic regulation and highlight the potential role of antioxidants and active lifestyle interventions in promoting wellness and preventing muscle decline due to aging.